New Waqf Paradigm: Integration of Islamic Commercial Finance and Islamic Social Finance - Syamsuri; Penta Syahifah Dena; Yaumi Sa'adah; Fuadah Binti Johari (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2024)
This paper discusses critiques of Indonesia's commercially-based waqf management and recommends solutions to improve waqf management to be more in line with Islamic principles and provide broader benefits to society. Criticism of commercial waqf management which includes waqf funds, lack of transparency and non-compliance with sharia principles. This paper underscores the importance of changing the paradigm of waqf management to integrate Islamic Social Finance (ISF) and Islamic Commercial Finance (ICF) to achieve Islamic economic goals that include social benefits and general welfare. By using normative types of research and conceptual approaches. This integration is expected to create a more inclusive and stable financial system and help overcome social and economic problems in Indonesia. In addition, this paper also discusses the basic principles in waqf management and the important role of waqf in the development of Islamic society. Through the implementation of productive commercial-based waqf, it is expected to improve the overall welfare of Muslims and make a positive contribution to sustainable development in Indonesia. Keywords: Waqf Management, Integration of Islamic Commercial Finance, Islamic Social Financial, Waqf Social-Productive Model.